Tunable LED illumination for biological tissue imaging - Gryko, Łukasz; Lewandowski, Jakub (Photonics Letters of Poland, 2023)
The article presents the results of biological tissue imaging with a tunable broadband LED illuminator with adjustable color and correlated color temperature of white light characterized by high color rendering indices. Color imaging of tissue is the basis for diagnostic procedures in various disease states. For this reason, it is essential to optimize the illumination so that differences in tissue color are highlighted not only by improved color fidelity but also by high color contrast. Full Text: PDF References M.H. Tran, B. Fei, "Compact and ultracompact spectral imagers: technology and applications in biomedical imaging", J Biomed Opt 28, 4 (2023). CrossRef E.J.M. Baltussen, E.N.D. Kok, S.G.J. Brouwer de Koning, "Hyperspectral imaging for tissue classification, a way toward smart laparoscopic colorectal surgery", J Biomed Opt 24, 1 (2019). CrossRef N.T. Clancy, G. Jones, L. Maier-Hein, D.S. Elson, and D. Stoyanov, "Surgical spectral imaging", Med Image Anal 63, 101699 (2020). CrossRef R. Zhang, Z. Guo, Y. Chen, "A Deep Learning-Aided Remote Spectrally Tunable LED Light Source Integrated System", IEEE Trans Instrum Meas 72, 1 (2023). CrossRef P. Liu, H. Wang, Y. Zhang, "Investigation of self-adaptive LED surgical lighting based on entropy contrast enhancing method", Opt Commun 319, 133 (2014). CrossRef J. Shen, S. Chang, H. Wang, Z. Zheng, Light. "Optimising the illumination spectrum for enhancing tissue visualisation", Res. Technol. 51, 99 (2019). CrossRef K. Kameyama, T. Ohbayashi, K. Uehara, A. Koga, Y. Hata, "The Influence of Illumination Color on the Subjective Visual Recognition of Biological Specimens", Yonago Acta Med 63, 266 (2020). CrossRef H. Wang, R.H. Cuijpers, M. R. Luo, I. Heynderickx, and Z. Zheng, "Optimal illumination for local contrast enhancement based on the human visual system", J Biomed Opt 20, 015005 (2015). CrossRef J. Mundinger, K. Houser, "Adjustable correlated colour temperature for surgical lighting", Light. Res. Technol. 51, 280 (2019). CrossRef M.A. Ilișanu, F. Moldoveanu, A. Moldoveanu, "Multispectral Imaging for Skin Diseases Assessment—State of the Art and Perspectives", Sensor 23, 3888 (2023). CrossRef K.L. Hanlon, G. Wei, L. Correa-Selm, and J.M. Grichnik, "Dermoscopy and skin imaging light sources: a comparison and review of spectral power distribution and color consistency", J Biomed Opt 27, 080902 (2022). CrossRef O.V. Mamontov, A.V. Shcherbinin, R.V. Romashko, "Intraoperative Imaging of Cortical Blood Flow by Camera-Based Photoplethysmography at Green Light", Appl Sci 10, 6192 (2020). CrossRef F.J. Burgos-Fernández, T. Alterini, F. Diaz-Douton, L. Gonzales, C. Mateo, C. Mestre, J. Pujol, M.Vilaseca, "Reflectance evaluation of eye fundus structures with a visible and near-infrared multispectral camera", Biomed Opt Express 13, 3504 (2022). CrossRef D. Kapsokalyvas, N. Bruscino, "Spectral morphological analysis of skin lesions with a polarization multispectral dermoscope", Opt Express 21, 4826 (2013). CrossRef J. Yang, H. Xu, F. Zhang, Z. Wang, P. Xu, "Enhancing local color contrast by optimizing multichannel LED light sources", Opt. Eng. 57, 1 (2018). CrossRef N. Posner, A. Stefanidi, J. Hanhart, Biomed. Eng. Res. (2020). DirectLink U.J. Blaszczak, L. Gryko, A. Zajac, "Tunable white light source for medical applications", Proc. SPIE, 10445 (2017), CrossRef L. Gryko, U. J. Blaszczak, A.S. Zajac, "Colorimetric characterization of the tunable LED-based light source at the output of the homogenizing rod", Proc SPIE, 1080811 (2018). CrossRef U.J. Błaszczak, Ł. Gryko, A.S. Zając, "Characterization of multi-emitter tuneable led source for endoscopic applications", Metrol. Meas. Syst. 26, 153 (2019). CrossRef U.J. Błaszczak, M. Gilewski, Ł. Gryko, A.S. Zając, "Badanie wpływu sposobu zasilania na wybrane parametry optyczne zestawu diod elektroluminescencyjnych", Przeglad Elektrotechniczny 92, 150 (2016). CrossRef